Health and Psychological Predictors of Antibiotic Use in Infancy and Fathers’ Role - Marina Fuertes; Rita Almeida; Francisco Dionisio (European Journal of Investigation in Health, Psychology and Education)
Previous research has shown that antibiotic use during the first year is associated with infants’ difficult behavior, maternal low sensitivity, and infant insecure-ambivalent attachment. However, these results may depend on the extent and type of parental involvement, paternal stress related to infant care, or the infant’s exposure to infections. To explore this question, we analyzed the relationship between these factors and examined potential predictors of antibiotic use among demographic, health, and psychological variables. This study included 62 Portuguese infants and their fathers as participants. Demographic and health information was collected at birth, 3, 9, and 12 months. Father–infant interactive behavior was observed in free play at 3 months and infant attachment in Strange Situation at 12 months. Parental Stress and Parents’ Responsibility Scales were used at 9 and 12 months, respectively. Infants who received antibiotics in the first year were less cooperative, more difficult, and less passive in free-play interactions and were more likely to attend a center-based daycare than others. In this study, the predictors of antibiotic use are infant difficultness and daycare type.